Enhancing Preschool Language Acquisition Through Robotic Assistants: An Evaluation of Effectiveness, Engagement, and Acceptance - Santiago Berrezueta-Guzman; Maria Dolon-Poza (IEEE Access)
Effective early language learning is crucial in education, and finding innovative ways to support it can make a significant difference. This study examines how a robotic assistant can enhance English vocabulary learning for preschool children aged 4 to 6. The study was conducted in two preschools and involved 40 participants split into two groups. Performance assessments were conducted at three stages to evaluate vocabulary acquisition and sentence construction abilities. Results revealed that children interacting with the robot learned 23% more words than those taught through traditional methods, particularly in the early months of exposure. The data analysis, comprising quantitative evaluations of vocabulary learning and qualitative surveys of parents and teachers, highlighted increased engagement, ease of classroom integration, and strong acceptance of the robot. Despite challenges such as student distraction and the need for consistent teacher supervision, the findings demonstrate that robotic assistants complement traditional teaching methods, offering enhanced engagement and improved learning outcomes.